VO #033 Proposal of 800mm Dia shoring piles works at zone C of BRAC University new campus project - BUCG-ABC Joint Venture (Brac University, 2023)
This record consists of general correspondence regarding VO #033 proposal of 800mm Dia shoring piles works at zone C of BRAC University new campus project.